2018
DOI: 10.2196/10197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Web-Based Electronic Health Record on Behavioral Health Service Delivery for Children and Adolescents: Randomized Controlled Trial

Abstract: BackgroundElectronic health records (EHRs) have been widely proposed as a mechanism for improving health care quality. However, rigorous research on the impact of EHR systems on behavioral health service delivery is scant, especially for children and adolescents.ObjectiveThe current study evaluated the usability of an EHR developed to support the implementation of the Wraparound care coordination model for children and youth with complex behavioral health needs, and impact of the EHR on service processes, fide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…There is widespread agreement that the certified EHR is a lever to the care quality among hospitals which theoretically is helpful to improve service process and result in better patient experience. [9,41] Empirical evidence is needed to testify about the implications of certified EHR use on the patient experience in psychiatric hospitals. This study sought to explore association between certified EHR adoption and patient experience in U.S. psychiatric hospitals by assessing the disparities in patient perception between psychiatric hospitals with and without certified EHR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is widespread agreement that the certified EHR is a lever to the care quality among hospitals which theoretically is helpful to improve service process and result in better patient experience. [9,41] Empirical evidence is needed to testify about the implications of certified EHR use on the patient experience in psychiatric hospitals. This study sought to explore association between certified EHR adoption and patient experience in U.S. psychiatric hospitals by assessing the disparities in patient perception between psychiatric hospitals with and without certified EHR.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results showed that certified EHR adoption is positively related to the patient perception of the responsiveness of hospital staff. On the one hand, staff may be free from the manual task with digital technology and have more time for the attention to patient progress and subsequent problem solving; [45] on the other hand, certified EHR may assist mental health practitioners timely tracking the patient situation and behavior changes, manage risk with incident notification, and automatically remind staff of the upcoming events in the care plan [9]. All the efficient interaction between patients and mental health practitioners could potentially reduce their waiting time for services and thus improve their patient experience with responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, the field of medicine has evolved toward greater digitization of data in order to improve coordination and continuity of care [1,2]. Information and communication technologies have brought computer science into medical units; medical data collection software is now abundant, and its use is expanding into a variety of settings [2,3]. However, many clinicians view this new reliance on technology as an added burden to their existing workload [2,4-6].…”
Section: Introductionmentioning
confidence: 99%